New Student Admission Information System for PG TK Aisyiyah VI Candi Using the End-User Method - Sandy Ismayudha; Ika Ratna Indra Astutik; Suhendro Busono; Irwan Alnarus Kautsar (SaNa: Journal of Blockchain, NFTs and Metaverse Technology, 2025)
There is an increasing demand for educational institutions to digitize the New Student Admission (PPDB) process in order to improve transparency and ease of management and operations. PG TK Aisyiyah VI Candi, located in Durung Bedug Village, Candi District, Sidoarjo Regency, currently still implements conventional student admission procedures. This situation causes long waiting times, inefficient documentation processes, and the potential for errors in data recording and entry. This study designs a web-based information system infrastructure with an End User Development (EUD) approach that aims to improve service quality, reduce administrative burdens, and increase stakeholder satisfaction. The EUD approach is a good model because it allows non-technical staff to customize the system according to their operational needs without full dependence on technical assistance, while maintaining system agility through feedback from stakeholders. The main features of this system include online registration initiated by parents, data transmission for file sharing, student identity verification by the school, and an electronic registration process. Validation results show that the system is capable of performing key functions such as identity verification, digital form management, document validation, process monitoring, and management analytics. This infrastructure not only achieves technical optimization but also drives the advancement of digital transformation in early childhood education institutions.